Isolated Pancreatic Metastases of Renal Cell Carcinoma—A Paradigm of a Seed and Soil Mechanism: A Literature Analysis of 1,034 Observations - Sellner, Franz (Frontiers in Oncology, 2020)
Previously documented arguments in favour of for the suspected impact of a seed and soil mechanism in the development and progression of isolated pancreatic metastasis of renal cell carcinomas (isPM) are: 1.the uniform and independent from the side of the primary tumour distribution of isPM within the pancreas and 2. the similar survival rates for singular and multiple isPM. In addition, the present study adds new arguments that further confirm the importance of an seed-and-soil-mechanism in isPM: 1. Within the singular isPM, the size of the metastasis does not affect the overall survival; 2. Within the group of multiple isPMs, the overall survival does not depend on the number of metastases; 3. For synchronous and metachronous isPM, survival rates are also not different, and 4. Within the group of metachronous isPM there is also no correlation between the overall survival and interval until metastases occur. This unusual ineffectiveness of otherwise known risk factors of solid cancers can be explained plausibly by the hypothesis of a very selective seed and soil mechanism in isPM, which only allows embolised renal carcinoma cells in the pancreas to complete all steps required to grow into clinically manifest metastases. In all other organs, on the other hand, the body is able to eliminate the embolised tumour cells or at least put them into a dormant state for many years. This minimises the risk of occult micrometastases in distant organs, which could later - after isPM treatment - grow into clinically manifest metastases, so that the prognosis of the isPM is only determined by an adequate therapy of the pancreatic foci, and prognostic factors such as total tumour burden or interval until the occurrence of the isPM remain ineffective.